Separation and identification of diacylglycerols containing branched chain fatty acids by liquid chromatography-mass spectrometry - Palyzová, Andrea; Řezanka, Tomáš (Journal of chromatography. A, 2021)
A combination of two chromatographic and two enzymatic methods was used for the analysis of molecular species of lipids from Gram-positive bacteria of the genus Kocuria. Gram-positive bacteria contain a majority of branched fatty acids (FAs), especially iso- and/or anteiso-FAs. Two strains K. rhizophila were cultivated at three different temperatures (20, 28, and 37°C) and the majority phospholipid, i.e., the mixture of molecular species of phosphatidylglycerols (PGs) was separated by means of hydrophilic interaction liquid chromatography (HILIC). After enzymatic hydrolysis of PGs by phospholipase C and derivatization of the free OH group, the sn-1,2-diacyl-3-acetyl triacylglycerols (AcTAGs) were separated by reversed phase HPLC. Molecular species such as i-15:0/i-15:0/2:0, ai-15:0/ai-15:0/2:0, and 15:0/15:0/2:0 (straight chains) were identified by liquid chromatography-positive electrospray ionization mass spectrometry. The tandem mass spectra of both standards and natural compounds containing iso, anteiso and straight chain FAs with the same carbons were identical. Therefore, for identification of the ratio of two regioisomers, i.e. i-15:0/ai-15:0/2:0 vs. ai-15:0/i-15:0/2:0, they were cleavage by pancreatic lipase. The mixture of free fatty acids (FFAs) and 2-monoacylglycerols (2-MAGs) was obtained. After their separation by TLC and esterification and/or transesterification, the fatty acid methyl esters were quantified by GC-MS and thus the ratio of regioisomers was determined. It has been shown that the ratio of PG (containing as majority i-15: 0 / i-15: 0, i-15: 0 / ai-15: 0 and / or ai-15: 0 / i-15: 0 and ai-15: 0 / ai-15: 0 molecular species) significantly affected the membrane flow of bacterial cells cultured at different temperatures.
Keywords: Chromatography, High Pressure Liquid; chemické techniky analytické; Chromatography, Liquid; vysokoúčinná kapalinová chromatografie; Gram-positive bacteria; RP-HPLC/MS-ESI(+); Hydrophobic and Hydrophilic Interactions; Fatty Acids; branched fatty acids; hmotnostní spektrometrie s elektrosprejovou ionizací; phosphatidylglycerols; mastné kyseliny; plynová chromatografie s hmotnostně spektrometrickou detekcí; enzymatic hydrolysis; chromatografie kapalinová; Chemistry Techniques, Analytical; Phospholipids; diacylglycerols; fosfolipidy; Diglycerides; Spectrometry, Mass, Electrospray Ionization; Gas Chromatography-Mass Spectrometry; Micrococcaceae; diglyceridy; hydrofobní a hydrofilní interakce